KEMAJUAN PEREMPUAN: BEBERAPA ASPEK KEPENDUDUKAN DAN SOSIAL BUDAYA - Singarimbun Masri (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1991)
The Indonesian women have achieved substantial progress over the last few decades and their participation in education, family planning, the labour force, and public life is relatively high by Asian standards. Literacy of women has incresed from 50.3 percent in 1971 to 78.6 percent in 1990; total fertility rates dropped from 5.6 in 1971 to 3-1 in 1991; infant mortality dropped from 143 in 1971 to 70 in 1985; female labour participation rates increased from 32.7 percent in 1980 to 39.2 percent in 1990; the ratio of male to female civil servants dropped from 3-6 in 1978 to 2.1 in 1990.The ratio of male to female member of parliament in Indonesia is lower than Singapore, Malaysia, USA, and Japan. However, many problems should be overcome before Indonesianwomen become fully integrated innational life.